Multi-element determination of calcium, potassium and magnesium in medicinal plant by high-resolution continuum source atomic absorption spectrometry - Silva, Tiago Varão; Rêgo, Jardes Figuerêdo; de Moraes, Mercedes; Cavalheiro, Alberto José; Gomes Neto, José Anchieta; Raposo Júnior, Jorge Luiz (Eclética Química, 2014)
A simple and rugged method to determine Ca, K and Mg in a single aliquot of medicinal plants by high-resolution continuum source flame atomic absorption spectrometry is proposed. Secondary lines for Ca (239.856 nm) and K (404.414 nm), and the alternate line measured at wing of the secondary line for Mg at 202.588 nm allowed calibration within the 20 – 500 mg L-1 Ca and K, and 1.0 – 80 mg L-1 Mg. Twenty samples and three plant certified materials were analyzed. Results were in agreement at a 95% confidence level with reference values. Limits of detection were 2.4 mg L-1 Ca, 1.9 mg L-1 K and 0.3 mg L-1 Mg. The RSD (n=12) were ≤ 5.1% and recoveries were between 83 and 108% for all analytes.